A HAPPY IMMORALIST: THE CASE OF RICHARD RICH. Issue 61 (2022) - Cahn, Steven M.
Abstract : Many philosophers, past and present, have been loath to admit the possibility of a happy immoralist. Here is a historical case featured in the play and film A Man for All Seasons.